Pulmonary Artery Pressure–Guided Heart Failure Management Reduces 30-Day Readmissions - Adamson, Philip B.; Abraham, William T.; Stevenson, Lynne Warner; Desai, Akshay S.; Lindenfeld, JoAnn; Bourge, Robert C.; Bauman, Jordan (Circulation. Heart failure, 2016)
This study examines the impact of pulmonary artery pressure-guided heart failure (HF) care on 30-day readmissions in Medicare-eligible patients. The CardioMicroelectromechanical system (CardioMEMS) Heart Sensor Allows Monitoring of Pressures to Improve Outcomes in New York Heart Association Class III Heart Failure Patients (CHAMPION) Trial included 550 patients implanted with a permanent MEMS-based pressure sensor in the pulmonary artery. Subjects were randomized to a treatment group (uploaded pressures were made available to investigators) or a control group (uploaded pressures were not made available to investigators). This analysis focuses on the 245 Medicare-eligible subjects for whom compliance with daily transmissions was 93% compared with 88% for the overall population. Medications were changed more often in the treatment group using pressure information compared with the control group using symptoms and daily weights alone. During the 515 days follow-up after implant, the overall rate of HF hospitalizations was 49% lower in the treatment group (60 HF hospitalizations, 0.34 events/patient-year) compared with control (117 HF hospitalizations, 0.67 events/patient-year; hazard ratio 0.51, 95% confidence interval 0.37-0.70; P<0.0001). Of the 177 HF hospitalizations, 155 qualified as an index HF hospitalization. All-cause 30-day readmissions were 58% lower in the treatment group (0.07 events/patient-year) compared with 0.18 events/patient-year in the control group (hazard ratio 0.42, 95% confidence interval 0.22-0.80; P=0.0080). Pulmonary artery pressure-guided HF management in Medicare-eligible patients led to a 49% reduction in total HF hospitalizations and a 58% reduction in all-cause 30-day readmissions. http://www.clinicaltrials.gov. Unique identifier: NCT00531661.